(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Lorenzo Tomatis was a great doctor in the broadest sense: he gave a major contribution to cancer research, devoting himself to study cancer causes and prevention. His job was not only to serve Public Health but to denounce social and health inequalities without threats by political and economic constraints.